Role of ICU-acquired weakness on extubation outcome among patients at high risk of reintubation - Thille, Arnaud W.; Boissier, Florence; Muller, Michel; Levrat, Albrice; Bourdin, Gaël; Rosselli, Sylvène; Frat, Jean-Pierre; Coudroy, Rémi; Vivier, Emmanuel (Critical care (London, England), 2020)
Background Whereas ICU-acquired weakness may delay extubation in mechanically ventilated patients, its influence on extubation failure is poorly known. This study aimed at assessing the role of ICU-acquired weakness on extubation failure and the relation between limb weakness and cough strength. Methods A secondary analysis of two previous prospective studies including patients at high risk of reintubation after a planned extubation, i.e., age greater than 65 years, with underlying cardiac or respiratory disease, or intubated for more than 7 days prior to extubation. Patients intubated less than 24 h and those with a do-not-reintubate order were not included. Limb and cough strength were assessed by a physiotherapist just before extubation. ICU-acquired weakness was clinically diagnosed as limb weakness defined as Medical Research Council (MRC) score < 48 points and severe weakness as MRC sum-score < 36. Cough strength was assessed using a semi-quantitative 5-Likert scale. Extubation failure was defined as reintubation or death within the first 7 days following extubation. Results Among 344 patients at high risk of reintubation, 16% experienced extubation failure (56/344). They had greater severity and lower MRC sum-score (41 ± 16 vs. 49 ± 13, p < 0.001) and were more likely to have ineffective cough than the others. The prevalence of ICU-acquired weakness at the time of extubation was 38% (130/244). The extubation failure rate was 12% (25/214) in patients with no limb weakness vs. 18% (12/65) and 29% (19/65) in those with moderate and severe limb weakness, respectively ( p < 0.01). MRC sum-score and cough strength were weakly but significantly correlated (rho = 0.28, p < .001). After multivariate logistic regression analyses, the lower the MRC sum-score the greater the risk of reintubation; severe limb weakness was independently associated with extubation failure, even after adjustment on cough strength and severity at admission. Conclusion ICU-acquired weakness was diagnosed in 38% in this population of patients at high risk at the time of extubation and was independently associated with extubation failure in the ICU.